Job Insecurity, Work Environment, and Job Satisfaction: An Investigation with a Mediating Role of Job Stress: Ketidakamanan Kerja, Lingkungan Kerja, dan Kepuasan Kerja: Investigasi dengan Peran Mediasi Stres Kerja. - Denny Andrea Selan; Rifdah Abadiyah (Universitas Muhammadiyah Sidoarjo, 2024)
This quantitative study aims to investigate the impact of job insecurity and work environment on job satisfaction, with job stress serving as the mediating variable, within the context of a manufacturing company. Data were collected from 54 employees through questionnaire surveys. The findings reveal that job insecurity and work environment have a significant influence on job satisfaction, with work-related stress playing a significant mediating role. Interestingly, job insecurity and work environment do not directly affect job satisfaction, but their effects are mediated by job stress. These results shed light on the complex interplay of factors influencing job satisfaction and highlight the importance of addressing job stress to enhance overall employee well-being and satisfaction in the workplace. Highlights: Job stress mediates the relationship between job insecurity and work environment with job satisfaction. Quantitative study conducted in a manufacturing company with 54 employee participants. Findings emphasize the importance of addressing job stress to enhance employee well-being and satisfaction in the workplace. Keywords: Job Insecurity, Work Environment, Job Satisfaction, Job Stress, Mediation